Developing a biomechanical model to identify the performance parameters In rowing - Zidouh, H.; Saffaj, N.; El-Moudny, S. (International Journal of Engineering & Scientific Research, 2019)
We have developed a biomechanical computational model to simulate the movement of the rower in order to identify the performance parameters in rowing. One novice rower was directed to row at rating steps of 30 cpm in instrumented Concept II Model C rowing ergometer. The rower movements are recorded with the opto-electronic system Vicon. The humanoid model is composed of 4 simple open kinematic chains representing arms and legs. Each chain is made up of 7 degrees of freedom (3 dof for the hip and the shoulder, 2 dof for the knee and the elbow, 2 dof for the ankle and the wrist). These four chains are connected to a body of reference grouping the pelvis, the trunk and the head together. The spatial orientation of the pelvis, the trajectory of the origin of the coordinate system linked to the pelvis and the joint angles allow the simulation of the movement of the rower.